Fluorescent Mueller-matrix polarimetry of biological tissues in differentiation of benign and malignant tumors - Ushenko, Yu.O.; Lakusta, I.I.; Olar, O.I.; Novakovska, O.Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The work is aimed at investigation of diagnostic efficiency provided by a new azimuthally stable Mueller-matrix method for analyzing laser fluorescence coordinate distributions characterizing biological tissue histological sections. A new model of generalized optical anisotropy of biological tissues containing protein networks has been proposed in order to ascertain the processes of laser autofluorescence. The influence of complex mechanisms of both phase anisotropy (linear birefringence and optical activity) and linear (circular) dichroism was taken into account. The interrelations between the azimuthally stable Mueller-matrix elements characterizing laser autofluorescence and different mechanisms of optical anisotropy have been determined. The statistic analysis of coordinate distributions of these Mueller-matrix rotation invariants has been offered. Thereupon the quantitative criteria (statistic moments of the 1st to 4th orders) of differentiation of histological sections of uterus wall tumor – group 1 (dysplasia) and group 2 (adenocarcinoma) have been estimated.